ANALISIS STRATEGI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) LAUNDRY DALAM MENGHADAPI PERSAINGAN - Matua Siregar, Haposan; Rohima, Rohima; Azura Fahani, Tania; Zaenab , Zaenab; Hayati, Fitri (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to analyze the development strategy of laundry Micro, Small and Medium Enterprises (MSME) in facing increasingly fierce competition. Laundry MSME, as one of the business sectors with great potential, often face serious challenges, such as limited capital, low use of technology, and inconsistent service quality. This research uses a qualitative approach with a case study method on several laundry MSMEs in urban areas, which are analyzed using the Swot theoretical framework and Porter's Five Forces model. The results showed that MSME laundry has strengths in competitive pricing, proximity to customers, and strategic location. However, the main weakness found is the lack of technology utilization and innovation in services, which hinders the competitiveness of the business. Opportunities, such as increasing awareness of sustainability-based services and digitalization, provide room for business development. Threats from competition with laundry franchises and changing customer preferences that increasingly lead to fast and efficient services, pose serious challenges for MSMEs. Based on the analysis, suggested development strategies include utilizing digital technology for management and marketing, improving service quality, innovation in service types, and product diversification to attract new customers.